Fully self‐gated free‐running 3D Cartesian cardiac CINE with isotropic whole‐heart coverage in less than 2 min. (25th September 2020) - Küstner, Thomas; Bustin, Aurelien; Jaubert, Olivier; Hajhosseiny, Reza; Masci, Pier Giorgio; Neji, Radhouene; Botnar, René; Prieto, Claudia
Abstract : Purpose: To develop a novel fast water‐selective free‐breathing 3D Cartesian cardiac CINE scan with full self‐navigation and isotropic whole‐heart (WH) coverage. Methods: A free‐breathing 3D Cartesian cardiac CINE scan with a water‐selective balanced steady‐state free precession and a continuous (non‐ECG‐gated) variable‐density Cartesian sampling with spiral profile ordering, out‐inward sampling and acquisition‐adaptive alternating tiny golden and golden angle increment between spiral arms is proposed. Data is retrospectively binned based on respiratory and cardiac self‐navigation signals. A translational respiratory‐motion‐corrected and cardiac‐motion‐resolved image is reconstructed with a multi‐bin patch‐based low‐rank reconstruction (MB‐PROST) within about 15 min. A respiratory‐motion‐resolved approach is also investigated. The proposed 3D Cartesian cardiac CINE is acquired in sagittal orientation in 1 min 50 s for 1.9 mm 3 isotropic WH coverage. Left ventricular (LV) function parameters and image quality derived from a blinded reading of the proposed 3D CINE framework are compared against conventional multi‐slice 2D CINE imaging in 10 healthy subjects and 10 patients with suspected cardiovascular disease. Results: The proposed framework provides free‐breathing 3D cardiac CINE images with 1.9 mm 3 spatial and about 45 ms temporal resolution in a short acquisition time (<2 min). LV function parameters derived from 3D CINE were in good agreement with 2D CINE (10 healthy subjects and 10 patients). Bias and confidence intervals were obtained for end‐systolic volume, end‐diastolic volume and ejection fraction of 0.1 ± 3.5 mL, −0.6 ± 8.2 mL and −0.1 ± 2.2%, respectively. Conclusion: The proposed framework enables isotropic 3D Cartesian cardiac CINE under free breathing for fast assessment of cardiac anatomy and function. Abstract : Free‐breathing continuous acquisitions, so called free running, enable whole‐heart coverage for motion‐resolved functional cardiac MRI. We propose a 3D Cartesian free‐running water‐selective balanced steady‐state free precession sequence that provides isotropic 3D whole‐heart CINE imaging in less than 2 min. Data is acquired with a variable‐density spiral‐like 3D Cartesian out‐inward sampling and sequence‐adaptive tiny golden and golden angle increment. Respiratory‐motion‐corrected and cardiac‐motion‐resolved images are obtained via full self‐gating and from a multi‐bin PROST reconstruction. Good agreement with 2D CINE was achieved.